Do perceived risk and perceived value impact the adoption of cashless system? - Salomo, Oloan; Giriati, Giriati; Syahputri, Anggraini; Malini, Helma; Azazi, Anwar (Junal Ilmu Manajemen, 2025)
For the modernization of society, the adoption of technology is needed. It is very important to understand the factors that influence society's behavior toward accepting cashless system technology. People make risks and benefits as decision-making materials. In this study, we use internal factors from the UTAUT model and the influence of perceived risk and perceived value as intervening variables on the intention to use cashless systems. To collect data, we distributed questionnaires online, resulting in 119 samples that we used for further tests. The results of this study indicate that effort expectancy and perceived value have a direct influence on the intention to use cashless systems, while performance expectancy and perceived risk do not. The results of the Sobel test show that performance expectancy and effort expectancy have an influence on the intention to use cashless systems with perceived value as an intervening variable. From these results, cashless system technology providers maximize benefits, especially in ease of use. The disadvantage of this study is that the number of samples is not too large.